Long-Term Peridialytic Blood Pressure Patterns in Patients Treated by Hemodialysis and Hemodiafiltration - Rootjes, Paul A. (Kidney Int Rep, 2020)
INTRODUCTION: Online postdilution hemodiafiltration (HDF) is associated with a lower all-cause and cardiovascular mortality than hemodialysis (HD). This may depend on a superior peridialytic (pre- and postdialysis, and the difference between these 2 parameters) hemodynamic profile. METHODS: In this retrospective cohort analysis of individual participant data (IPD) from 3 randomized controlled trials (RCTs) (n = 2011), the effect of HDF and HD on 2-year peridialytic blood pressure (BP) patterns was assessed. Long-term peridialytic systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and pulse pressure (PP), as well as the deltas (post- minus predialytic) were assessed in the total group of patients. Thereafter, these variables were compared between patients on HD and HDF, and in the latter group between quartiles of convection volume. RESULTS: Mean pre- and postdialysis SBP, DBP, and MAP declined significantly during follow-up (predialytic: SBP −2.16 mm Hg, DBP −2.88 mm Hg, MAP −2.64 mm Hg), PP increased (predialytic 0.96 mm Hg). Peridialytic deltas remained unaltered. Differences between the 2 modalities, or between quartiles of convection volume were not observed. BP changes were independent of various baseline characteristics, including the decline in body weight over time. CONCLUSION: We speculate that the combination of a decreasing SBP and an increasing PP may be the clinical sequelae of a worsening cardiovascular system. Because especially HDF with a high convection volume has been associated with a beneficial effect on survival, our study does not support the view that superior peridialytic BP control contributes to this effect.